Joint Motion Quality in Chondromalacia Progression Assessed by Vibroacoustic Signal Analysis. Issue 11 (6th April 2016) - Bączkowicz, Dawid; Majorczyk, Edyta
Abstract: Background: Because of the specific biomechanical environment of the patellofemoral joint, chondral disorders, including chondromalacia, often are observed in this articulation. Chondromalacia via pathologic changes in cartilage may lead to qualitative impairment of knee joint motion. Objective: To determine the patellofemoral joint motion quality in particular chondromalacia stages and to compare with controls. Design: Retrospective, comparative study. Setting: Voivodship hospitals, university biomechanical laboratory. Patients: A total of 89 knees with chondromalacia (25 with stage I; 30 with stage II and 34 with stage III) from 50 patients and 64 control healthy knees (from 32 individuals). Methods: Vibroacoustic signal pattern analysis of joint motion quality. Main Outcome Measurements: For all knees vibroacoustic signals were recorded. Each obtained signal was described by variation of mean square, mean range (R4), and power spectral density for frequency of 50‐250 Hz (P1) and 250‐450 Hz (P2) parameters. Results: Differences between healthy controls and all chondromalacic knees as well as chondromalacia patellae groups were observed as an increase of analyzed parameters ( P < .001) with only one exception. No statistically significant difference between control group and stage I of chondromalacia patellae was found. All chondromalacia groups were differentiated by the use of all analyzed parameters ( P < .01), whose values correspond to the progress of chondromalacia. Conclusions: Chondromalacia generates abnormal vibroacoustic signals, and there seems to be a relationship between the level of signal amplitude as well as frequency and cartilage destruction from the superficial layer to the subchondral bone. Level of Evidence: IV